Risk Factors and Stress Management Among Hospital Nurses: A Systematic Review - Unggul Widodo, I; ., Pujiyanto (KnE Life Sciences, 2019)
Work stress has become one of the most severe health problems in the twenty-first century. Work stress occurs in many workers in the health sector since high levels of individual responsibility make health workers vulnerable to pressure. The amount of work stress experienced by nurses is predicted to continue to increase in the years to come. The is a trend that cannot be ignored because it is very closely related to the safety of both nurses and patients. The purpose of this review is to look at the risk factors for work stress in nursing and at the stress-management approaches that are used to address them. The method used was a database search, using keywords, of ProQuest, ScienceDirect, and Google Scholar. The search yielded six studies that met the criteria. The results of the review show that the risk factors for stress in various countries are very diverse, ranging from high workload to high anxiety about patients. Work stress arises because of an imbalance between the personality characteristics of employees (personal factors) and the characteristics of their work situation (work environment and organizational factors). Hence, there are two approaches to the management of work stress, namely the individual plan and the regulatory strategy. In some countries, the organizational approach to stress management is very similar to the different approach. Stress management using the personal approach appears to be quite useful in reducing levels of stress and anxiety in nurses, and it can thus contribute to making an individual a better public health nurse. Keywords: work stress, nurses, risk factors, stress management